2018
DOI: 10.3390/genes9080377
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Roles of Susceptibility Loci for Autoimmune Diseases in the Post-GWAS Era

Abstract: Although genome-wide association studies (GWAS) have identified several hundred loci associated with autoimmune diseases, their mechanistic insights are still poorly understood. The human genome is more complex than single nucleotide polymorphisms (SNPs) that are interrogated by GWAS arrays. Apart from SNPs, it also comprises genetic variations such as insertions-deletions, copy number variations, and somatic mosaicism. Although previous studies suggest that common copy number variations do not play a major ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 118 publications
0
12
0
Order By: Relevance
“…There are numerous polymorphisms that affect the immune system. These have been linked to autoimmune diseases such as multiple sclerosis and type I diabetes (193) but not to ALS (194). However, it would seem likely that genetic variation in immune genes could influence the immune abnormalities described above, For example, polymorphisms in cytokine genes can influence the levels of cytokines such as IL-6, (195) and TNFα (196) and the IL33/ST2 pathway (197).…”
Section: Immunogenetics Of Alsmentioning
confidence: 99%
“…There are numerous polymorphisms that affect the immune system. These have been linked to autoimmune diseases such as multiple sclerosis and type I diabetes (193) but not to ALS (194). However, it would seem likely that genetic variation in immune genes could influence the immune abnormalities described above, For example, polymorphisms in cytokine genes can influence the levels of cytokines such as IL-6, (195) and TNFα (196) and the IL33/ST2 pathway (197).…”
Section: Immunogenetics Of Alsmentioning
confidence: 99%
“…However, autoimmune disease in humans is relatively common, and the genetics of predisposition is complex, polygenic, and heavily influenced by environmental factors. Hundreds of genetic loci influencing susceptibility to various autoimmune and inflammatory disorders have been discovered by genome-wide association studies (GWAS) in humans, and in many cases have confirmed mouse models and yielded novel insights into mechanisms underpinning disease (2). Despite this, the identity of causal variants and their target genes remain largely unknown because variants rarely alter protein coding sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Women mount a more vigorous immune response and are more susceptible to most autoimmune diseases 1,2 . These diseases have a strong but complex genetic component, and it has been di cult to identify the underlying polymorphisms [3][4][5] . The female preponderance in autoimmunity is sex hormone related 6 but could also be genetically dependent 7 .…”
Section: Introductionmentioning
confidence: 99%